The effect of antipsychotics on glutamate levels in the anterior cingulate cortex and clinical response: A 1H-MRS study in first-episode psychosis patients - Zahid, Uzma; McCutcheon, Robert A.; Borgan, Faith; Jauhar, Sameer; Pepper, Fiona; Nour, Matthew M.; Rogdaki, Maria; Osugo, Martin; Murray, Graham K.; Hathway, Pamela; Murray, Robin M.; Egerton, Alice; et al. (Frontiers in Psychiatry, 2022)
Introduction: Glutamatergic dysfunction is implicated in the pathophysiology of schizophrenia. It is unclear whether glutamatergic dysfunction predicts response to treatment or if treatment normalises this. We investigated the effect of antipsychotic treatment on glutamatergic levels in the anterior cingulate cortex (ACC), and whether there is a relationship between baseline glutamatergic levels and clinical response after antipsychotic treatment in people with first episode psychosis (FEP). Methods: The sample comprised 25 FEP patients; 22 completed magnetic resonance spectroscopy scans at both timepoints. Symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS). Results: There was no significant change in glutamate (baseline M = 13.23, SD = 2.33; follow-up M = 13.89, SD = 1.74; t(21)= -1.158, p = 0.260), or Glx levels (baseline M = 19.64, SD = 3.26; follow-up M = 19.66, SD = 2.65; t(21)= -0.034, p = 0.973). There was no significant association between glutamate or Glx levels at baseline and the change in PANSS positive (Glu r = 0.061, p = 0.777, Glx r = -0.152, p = 0.477), negative (Glu r = 0.144, p = 0.502, Glx r = 0.052, p = 0.811), general (Glu r = 0.110, p = 0.607, Glx r = -0.212, p = 0.320) or total scores (Glu r = 0.078, p = 0.719 Glx r = -0.155, p = 0.470). Conclusions: These findings indicate that treatment response is unlikely to be associated with baseline glutamatergic metabolites prior to antipsychotic treatment, and there is no major effect of antipsychotic treatment on glutamatergic metabolites in the ACC.